Username : Evie - Sugg, Joe (London Hodder & Stoughton, 2015)
A socially-isolated teenage girl is given the opportunity to save a virtual world from descending into chaos. All the while, she must fend off high school bullies and help her ailing father.
Including illustration
Keywords: Virtual reality -- Teenage girls